Concordance between the Hysteroscopic Diagnosis of Endometrial Hyperplasia and Histopathological Examination - Pasquale De Franciscis (Diagnostics, 2019)
The goal of this paper is to assess the concordance between the clinical diagnosis of Endometrial Hyperplasia (EH), suspected by senior gynecologists throughout outpatient office hysteroscopy, and the results from histopathological examination, in order to evaluate hysteroscopic accuracy for EH. A prospective cohort study was done at a Tertiary University Hospital. From January to December 2018, we enrolled women with the following criteria: abnormal uterine bleeding in post-menopause and endometrial thickening in pre-or post-menopause. Patients underwent office hysteroscopy with a 5 mm continuous-flow hysteroscope, and endometrial biopsies were taken using miniaturized instruments. Senior operators had to foresee histopathological diagnosis using a questionnaire. Histopathological examination was conducted to confirm the diagnosis. This study was approved by the local ethical and registered in the ClinicalTrials.gov registry (ID no. NCT03917147). In 424 cases, 283 clinical diagnoses of EH were determined by senior surgeons. A histopathological diagnosis was then confirmed in 165 cases (58.3%; p = 0.0001). Furthermore, 14 endometrial carcinoma and atypical hyperplasia were found. The sensitivity, positive predictive value, and negative predictive values for EH were, respectively, 90.4, 58.4, and 86.6%. Subdivided by clinical indication, the sensitivity was higher in patients with post-menopause endometrial thickening. The diagnostic accuracy of office hysteroscopy in the diagnosis and prediction of endometrial hyperplasia was high. Senior operators could foresee EHs in more than half the cases.